Spiritualitas dan Budaya dalam Akuntansi Biaya Dodol - Mohamad Anwar Thalib; Rifdayanti Paungan; Nurhayati Ntuka; Rohali R Tuna (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This paper examines cost accounting practices among dodol sellers by highlighting that accounting is not merely a technical activity but one that is embedded in cultural and spiritual values. The background of this study lies in the unique integration of morality, religiosity, and local Gorontalo wisdom within everyday cost-related decisions, making this topic both relevant and academically compelling. The study employs a qualitative approach grounded in Islamic ethnomethodology, analyzed through five stages: charity, knowledge, faith, revealed information, and courtesy. Data were gathered through direct observations and in-depth interviews with dodol sellers to understand how cost accounting is practiced in real contexts without speculation or unnecessary interpretation. The findings reveal four empirical practices: managing labor and raw material costs, controlling production costs, memory-based record-keeping, and simple paper-based documentation. These practices reflect honesty and ethical conduct, illustrated by the Gorontalo proverb “dahayi moputu dila” (guard your tongue, do not be dishonest). The study concludes that cost accounting among dodol sellers is culturally and spiritually grounded. The implication is twofold: theoretically, it broadens the conceptualization of accounting; practically, it offers an alternative cost accounting model for MSMEs that is rooted in local wisdom. The main takeaway is that cost accounting can serve not only as a technical tool but also as a reflection of ethical and spiritual practices.